Ferulic Acid Ameliorates Atherosclerotic Injury by Modulating Gut Microbiota and Lipid Metabolism - Gu, Yuyan; Zhang, Yaxin; Li, Mei; Huang, Zhiyong; Jiang, Jing; Chen, Yihao; Chen, Junqi; Jia, Yuhua; Zhang, Lihua; Zhou, Fenghua (Frontiers in Pharmacology, 2021)
Atherosclerosis is a leading cause of death worldwide. Recent studies have emphasized the significance of gut microbiota and lipid metabolism in the development of atherosclerosis. Herein, the effects and molecular mechanisms involving ferulic acid (FA) was examined in atherosclerosis using the ApoE-knockout (ApoE-∕-, c57BL/6 background) mouse model. Eighteen male ApoE−/− mice were fed a high-fat diet (HFD) for 12 weeks and then randomly divided into three groups: the model group, the FA (40 mg/kg/day) group and simvastatin (5 mg/kg/day) group. As results, FA could significantly alleviate atherosclerosis and regulate lipid levels in mice. Liver injury and hepatocyte steatosis induced by HFD were also mitigated by FA. FA improved lipid metabolism involving up-regulation of AMPKα phosphorylation and down-regulation of SREBP1 and ACC1 expression. Furthermore, FA induced marked structural changes in the gut microbiota and fecal metabolites and specifically reduced the relative abundance of Fimicutes, Erysipelotrichaceae and Ileibacterium, which were positively correlated with serum lipid levels in atherosclerosis mice. In conclusion, we demonstrate that FA could significantly ameliorate atherosclerotic injury, which may be partly by modulating gut microbiota and lipid metabolism via the AMPKα/SREBP1/ACC1 pathway.